Pengaruh Pemberian Extrak Jahe Dan Kacang Hijau Terhadap Pengurangan Mual Pada Ibu Hamil Semester 1 Di Puskesmas Ngawen 2 Wonosari Gunung Kidul - Sih Rini Handajani; KH Endah Widhi Astuti (Poltekkes Kemenkes Surakarta, 2019)
Background: Nausea and vomiting are common discomforts experienced by 50% of pregnant women. Emesis gravidarum will gain weight into hyperemesis gravidarum. Management to overcome the discomfort of nausea and vomiting in the first trimester of pregnancy is to use pharmacological and non-pharmacological therapies including ginger drink and green beans. The purpose of this study was to determine the effect of ginger drink and green beans on the frequency of nausea and vomiting in trimester pregnant women. Methods: Used in this study was quasy experiment with a time series pretest-posttest design approach. The population in this study was TM I pregnant women in the Ngawen II health center. The sample in this study was first trimester pregnant women who experienced nausea and vomiting. The analysis of this study used the Wilcoxon and Kruskal-wallis test. Results: Showed there was an effect of giving ginger drink and green beans to the frequency of nausea vomiting in first trimester pregnant women with p value 0.01 <α with ginger drink being the most influential in post hoc nausea frequency of vomiting 6.67 compared to green beans and standard drugs. Conclusion: Administration of ginger drink and green beans has an effect on reducing the frequency of nausea and vomiting in first trimester pregnant women.